PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. AIR MINUM TABALONG BERSINAR (PERSERODA) KABUPATEN TABALONG - Linda Mulyana Sari; Jauhar Arifin (JAPB, 2022)
The work environment is a place for a number of groups in which there are several supporting facilities to achieve company goals in accordance with the company's vision and mission. The work environment is divided into 2, namely the physical work environment and non-physical work environment. The physical work environment is all physical conditions that exist around the workplace that can affect employees either directly or indirectly. While the Non-Physical Work Environment is all conditions that occur related to work relations, both relations with superiors and relationships among co-workers, or relationships with subordinates. Good working conditions are expected to provide stimulation for employees, so as to encourage employees to be more productive and able to increase work effectiveness. This study aims to (1) determine the influence of the non-physical work environment on the effectiveness of employees at PT. Tabalong Drinking Water Shines (Perseroda) Tabalong Regency. (2) Knowing how much influence the non-physical work environment has on the work effectiveness of employees at PT. Tabalong Drinking Water Shines (Perseroda) Tabalong Regency. The type of research used is a quantitative approach, using the Generalized Structured Component Analysis (GSCA) analysis tool. This study used a population of 68 respondents. The sampling technique used saturated sampling, so that the sample in this study was 68 respondents. The results of this study indicate that 1) There is an influence of the non-physical work environment on the work effectiveness of employees at PT. Tabalong Drinking Water Shines (Perseroda) Tabalong Regency. 2) The magnitude of the influence of the Non-Physical Work Environment on the Work Effectiveness of employees at PT. Drinking Water Tabalong Shines (Perseroda) Tabalong Regency, namely 44.3% and the remaining 55.7% can be influenced by other variables. Keywords: Non-Physical Work Environment, Work Effectiveness, Generalized Structured Component Analysis (GSCA)